Solid porous polymer film for metal-air battery as well as preparation method and application of solid porous polymer film
By using solid porous polymer films in metal-oxygen batteries, the problems of low oxygen concentration and moisture and CO2 in air atmosphere are solved, and the long life and efficient performance of the battery in an air environment are achieved.
Patent Information
- Application Number
- CN202411611100.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-12
AI Technical Summary
When existing metal-oxygen batteries are used in air atmosphere, the oxygen concentration is low, the impact of moisture and CO2 on battery performance has not been fully resolved, and there are safety risks for the oxygen tank.
A solid porous polymer film is used as a gas separation membrane, and a film with oxygen-energized, hydrophobic and CO2 adsorption functions are prepared by a combination of fluoropolymer, polyethylene oxide and polyethyleneimine.
This film can stabilize the discharge and charging capacity of metal-air batteries, improve the cycle life of the battery, and reduce the impact of water vapor and CO2 on the battery.
Smart Images

Figure CN119481573A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal-air batteries, and in particular to a solid porous polymer membrane for metal-air batteries, and a preparation method and application thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] The energy density of traditional lithium-ion batteries is limited and the actual energy density is close to the theoretical energy density, which is far from meeting the needs of electric vehicles and energy storage. Metal-oxygen (air) batteries are the secondary batteries with the highest known theoretical energy density. They are also known as the ultimate batteries. They perform reversible charge and discharge cycles through the generation and decomposition of metal oxides. The positive active material of the metal-air battery comes from oxygen in the air or pure oxygen provided by oxygen tanks. According to the negative electrode material, it can include lithium-air batteries, sodium-air batteries, zinc-air batteries and aluminum-air batteries. Metal-air batteries are composed of air positive electrodes, electrolytes and metal negative electrodes. Its high energy density, low cost and environmental friendliness make it the most promising next-generation high-energy-density energy storage and power battery.
[0004] Although metal-air batteries have many advantages, in actual battery testing and operation, they are still mainly in the form of metal-oxygen batteries, which provide pure oxygen to the battery through oxygen cylinders. This battery system ignores the key issues of the impact of other components of air on battery performance, such as the corrosion of lithium negative electrodes by moisture in the air, the irreversible products generated by CO2 participating in the reaction, and the low oxygen concentration in the air. At the same time, when oxygen is provided to the battery through oxygen tanks, this not only increases the operating cost of the battery, but the oxygen tanks themselves are safety risks.
[0005] Therefore, it is an urgent problem to provide a metal-air battery protective membrane that is hydrophobic and can adsorb CO2 while ensuring an oxygen transmission channel, so that the metal-air battery has a longer service life in an air atmosphere. Summary of the invention
[0006] In view of this, the present invention provides a solid porous polymer membrane for a metal-air battery and a preparation method and application thereof. The solid porous polymer membrane provided by the present invention simultaneously satisfies the functions of oxygen permeability, hydrophobicity and CO2 adsorption, can stabilize the actual discharge and charging capacity of the metal-air battery, and improve battery performance such as battery cycle life.
[0007] In a first aspect, the present invention provides a method for preparing a solid porous polymer membrane for a metal-air battery, comprising the following steps:
[0008] A fluorine-containing polymer, polyethylene oxide and polyethyleneimine in a mass ratio of (2.5-2.7):(0.3-0.5):1 are dissolved in a solvent to form a casting solution, and then the casting solution is coated on the surface of a substrate, dried and placed in water for demolding, and dried to obtain a solid porous polymer membrane for a metal-air battery.
[0009] Preferably, the fluorine-containing polymer includes one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) or polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE).
[0010] Preferably, the weight average molecular weight of the fluorine-containing polymer is greater than 300,000, the weight average molecular weight of polyethylene oxide is greater than 800,000, and the weight average molecular weight of polyethyleneimine is 1,700-2,000.
[0011] Preferably, the solvent is selected from one or more of acetone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone; in the casting solution, the total mass fraction of the fluorinated polymer, polyethylene oxide, and polyethyleneimine is 10 to 20 wt%.
[0012] Preferably, the specific steps of the preparation process of the casting solution are as follows: adding the fluorine-containing polymer, polyethylene oxide and polyethyleneimine to a solvent, stirring at 40 to 60° C. for 3 to 6 hours to obtain the casting solution.
[0013] Preferably, in the step of coating the casting liquid on the substrate surface, the coating thickness is 400-600 μm; in the step of placing the film in water for demolding after drying, the drying temperature is 60-100° C.; and the time for demolding in water is 2-10 min.
[0014] Preferably, in the step of drying to obtain a solid porous polymer membrane for a metal-air battery, the drying temperature is 15 to 35°C.
[0015] In a second aspect, the present invention provides a solid porous polymer membrane for a metal-air battery prepared by the above preparation method.
[0016] In a third aspect, the present invention provides a solid porous polymer membrane for a metal-air battery prepared by the above preparation method or the use of the solid porous polymer membrane for a metal-air battery in a metal-air battery.
[0017] In a fourth aspect, the present invention provides a metal-air battery, comprising a positive electrode shell, a gas separation membrane, a positive electrode, an electrolyte layer, a metal negative electrode, a steel sheet, a spring sheet and a negative electrode shell in contact with each other in sequence; the gas separation membrane is a solid porous polymer membrane for a metal-air battery prepared by the above preparation method or the above solid porous polymer membrane for a metal-air battery.
[0018] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0019] The preparation method of the solid porous polymer membrane for metal-air batteries provided by the present invention is simple, and the solid porous polymer membrane with a hole morphology of suitable pore size can be prepared by the method, which can ensure the diffusion of oxygen necessary for the reaction, and can adsorb CO2, reduce the penetration of "impurity" gas CO2, and also has good hydrophobic properties, reducing the influence of water vapor on the metal-air battery. The application of the solid porous polymer membrane of the present invention in the metal-air battery can significantly improve the cycle life of the metal-air battery in an air environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 is a surface scanning electron microscope picture of the solid porous polymer membrane of Example 1 of the present invention, wherein a, the magnification is 1600, b, the magnification is 50000;
[0022] Figure 2 is a surface scanning electron microscope picture of the solid porous polymer membrane of Comparative Example 1 of the present invention, wherein a, the magnification is 1600, and b, the magnification is 16000;
[0023] Figure 3 is a surface scanning electron microscope image of the polymer film of Comparative Example 2 of the present invention;
[0024] Figure 4 It is a macroscopic photograph of the casting solution prepared in Comparative Example 3 (a), Example 1 (b), and Comparative Example 4 (c) of the present invention;
[0025] Figure 5 are macroscopic photographs of the solid porous polymer membranes of Comparative Example 3(a) and Example 1(b) of the present invention;
[0026] Figure 6This is a surface scanning electron microscope picture of the solid porous polymer membrane of Comparative Example 5 of the present invention; wherein a, the magnification is 500, b, the magnification is 40000;
[0027] Figure 7 is a schematic diagram of the assembly structure of a lithium-air battery in a test example of the present invention;
[0028] Figure 8 This is a graph showing the results of the first cycle deep discharge / charge test of a lithium-air battery assembled in a test example of the present invention;
[0029] Fig. 9 This is a graph showing the results of a constant capacity cyclic discharge / charge test of a lithium-air battery assembled in a test example of the present invention;
[0030] Fig.10 It is a schematic diagram of the working principle of the solid porous polymer membrane of Example 1 of the present invention when used as a gas separation membrane. DETAILED DESCRIPTION
[0031] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0032] The gas pressure and oxygen concentration of metal-air batteries operating in an air environment are low. At the same time, impurity gases (such as H2O and CO2) in the ambient air will generate side reaction products under electrochemical reactions, thus affecting the reaction. For example, water vapor in the air will corrode the metal lithium negative electrode and generate the side reaction product LiOH·H2O. Water vapor and CO2 in the air will also generate side reaction products LiOH and Li2CO3 on the positive electrode side of the battery. As the battery continues to discharge / charge, "dead lithium" will appear on the metal negative electrode, and other products will adhere to the surface of the positive electrode catalyst and the inside of the positive electrode, blocking the transmission channel of the reaction gas from the positive electrode to the electrolyte, reducing the actual discharge capacity of the battery and shortening the cycle life of the battery.
[0033] Therefore, the present invention provides a method for preparing a solid porous polymer membrane for a metal-air battery, comprising the following steps:
[0034] A fluorine-containing polymer, polyethylene oxide and polyethyleneimine in a mass ratio of (2.5-2.7):(0.3-0.5):1 are dissolved in a solvent to form a casting solution, and then the casting solution is coated on the surface of a substrate, dried and placed in water for demolding, and dried to obtain a solid porous polymer membrane for a metal-air battery.
[0035] The present invention uses fluorine-containing polymer as the main matrix material, which plays a supporting and hydrophobic role, blocking water vapor from entering the metal-air battery. The introduction of polyethylene oxide can make the solid porous polymer membrane have a good pore structure, thereby ensuring the smooth penetration of oxygen; if the addition amount of polyethylene oxide is too low, it will cause the membrane surface to be dense, which is difficult to apply in actual metal-air batteries; if the addition amount of polyethylene oxide is too high, it will not only have an adverse effect on the pore structure, but also cause the hydrophobicity of the solid porous polymer membrane to decrease. The introduction of polyethyleneimine can improve the adsorption of CO2 by the solid porous polymer membrane and reduce its effect on the reaction. The appropriate component mass ratio ensures that the solid porous polymer membrane has multiple functions of oxygen permeability, hydrophobicity and CO2 adsorption, thereby stabilizing the actual discharge and charging capacity of the metal-air battery and improving battery performance such as battery cycle life.
[0036] In the present invention, the fluorine-containing polymer includes one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) or polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE). In one or more embodiments of the present invention, the fluorine-containing polymer is selected from polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP).
[0037] In the present invention, the weight average molecular weight of the fluorine-containing polymer is greater than 300,000, the weight average molecular weight of polyethylene oxide is greater than 800,000, and the weight average molecular weight of polyethyleneimine is 1700 to 2000. Appropriate molecular weights can ensure good film-forming properties and high mechanical strength of the resulting film.
[0038] In the present invention, the solvent is selected from one or more of acetone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0039] In the present invention, the total mass fraction of the fluorine-containing polymer, polyethylene oxide and polyethyleneimine in the casting solution is 10-20wt%, more preferably 12-18wt%. The appropriate mass fraction can ensure that the casting solution has a suitable viscosity, which is beneficial to the subsequent coating and film forming process.
[0040] In the present invention, the specific steps of the preparation process of the casting solution are as follows: adding a fluorine-containing polymer, polyethylene oxide and polyethyleneimine to a solvent, stirring at 40 to 60° C. for 3 to 6 hours, and preparing a casting solution. The present invention finds that it is difficult to prepare a uniform and transparent casting solution by stirring at room temperature, and too long a stirring time or too high a stirring temperature will lead to gelation, and it cannot be used for subsequent experiments.
[0041] In the step of coating the casting solution on the substrate surface of the present invention, the coating thickness is 400-600 μm, so as to ensure that the thickness of the solid porous polymer membrane for the metal-air battery finally obtained is 80-300 μm. The appropriate thickness can balance the oxygen permeability, hydrophobicity and CO2 adsorption functions of the membrane. If the thickness is too thin, the adsorption and barrier performance of impurity gases will be insufficient. If the thickness is too thick, the oxygen permeability will be poor, affecting the efficiency of the electrochemical reaction.
[0042] In the present invention, in the step of coating the casting liquid on the surface of the substrate, the coating is selected from any one of casting, scraping, spraying, sprinkling or dripping, and the present invention does not impose any special restrictions on this; the material of the substrate can be a glass plate, a polytetrafluoroethylene mold, a metal plate, etc., and the present invention does not impose any special restrictions on this.
[0043] In the step of removing the film in water after drying, the drying temperature is 60-100° C. The drying time is not particularly limited as long as the solvent can be completely removed. The drying process is preferably vacuum drying.
[0044] The demoulding time in water is 2 to 10 minutes, which is to separate the dried film from the substrate and partially release the polyethylene oxide from the film to form holes. The demoulding time should not be too long, otherwise it will lead to the loss of polyethyleneimine.
[0045] In the step of drying to obtain the solid porous polymer membrane for metal-air batteries of the present invention, the drying temperature is 15-35° C., and the drying is preferably carried out in a natural drying manner to avoid curling and wrinkling of the wet membrane.
[0046] The present invention provides a solid porous polymer membrane for a metal-air battery prepared by the above preparation method, the surface of which has evenly distributed holes with a pore size of 100 to 500 nm.
[0047] The present invention also provides application of the solid porous polymer membrane for metal-air battery in metal-air battery.
[0048] The present invention also provides a metal-air battery, comprising a positive electrode shell, a gas separation membrane, a positive electrode, an electrolyte layer, a metal negative electrode, a steel sheet, a spring sheet and a negative electrode shell in contact with each other in sequence; the gas separation membrane is the solid porous polymer membrane for the metal-air battery.
[0049] In the present invention, the positive electrode shell, in addition to being a support and a conductive material, has its surface covered with small holes of uniform size and uniform distribution, providing a channel for air transmission. The steel sheet, spring sheet and negative electrode shell are present as support and conductive materials.
[0050] The present invention does not impose any special restrictions on the materials of the positive electrode, electrolyte layer, and metal negative electrode, and the materials commonly used in the art can be used. Preferably, the positive electrode includes a conductive support material and a catalyst layer, and the conductive support material includes but is not limited to hydrophilic and hydrophobic carbon paper, nickel foam, etc.; the catalyst material of the catalyst layer is two or more of acetylene black, carbon nanotubes, manganese dioxide (MnO2) or ruthenium dioxide (RuO2), and the loading amount of the catalyst material is 0.1-0.5 mg / cm 2 .
[0051] The electrolyte layer is located between the positive electrode and the metal negative electrode, and is composed of a glass fiber membrane that absorbs organic electrolytes of different concentrations, and can also be a solid electrolyte; the glass fiber membrane is a fiber diaphragm with a certain liquid absorption rate; the organic electrolyte is composed of a metal salt and an organic solvent, and the metal salt is determined by the metal negative electrode. For example, when the negative electrode is lithium metal, the metal salt is a lithium salt (including one or more of LiClO4, LiPF6, LiAsF6, LiTFSI, etc.); the organic solvent includes one or more of dimethyl sulfoxide, ether solvents, carbonate solvents, amide solvents and acetonitrile solvents, etc. The thickness of the electrolyte layer is 0.3 to 1 mm.
[0052] The metal negative electrode includes but is not limited to a lithium negative electrode, a magnesium negative electrode or a sodium negative electrode; the metal-air battery includes but is not limited to an all-solid-state metal-air battery, an organic electrolyte metal-air battery, a dual electrolyte metal-air battery, etc.
[0053] The technical solution of the present invention is further described below in conjunction with specific embodiments. The present invention has no particular restrictions on the source of the reagents used, and commercially available products known to those skilled in the art can be used. In the following examples, the weight average molecular weight of PVDF-HFP is 400,000, the weight average molecular weight of PEO is 1,000,000, and the molecular weight of PEI is 1,800.
[0054] Example 1
[0055] This embodiment provides a method for preparing a solid porous polymer membrane.
[0056] (1) Weigh 2.5 g of PVDF-HFP and 0.5 g of PEO, put them into a small beaker, drop 24 g of solvent (6 g of acetone, 18 g of DMF), put in a rotor, place it on a stirrer and stir at 400 r / min for 30 min, then add 1 g of PEI to the resulting slurry, then heat to 50 °C and stir at a speed of 400 r / min. After stirring for 5 h, a casting solution was obtained.
[0057] (2) The casting solution obtained in step (1) was coated on a transparent glass sheet (10 cm×10 cm×5.5 mm) using an infrared flatbed coater, with a coating height of 0.5 mm.
[0058] (3) Place the glass sheet coated with the casting solution in step (2) in a vacuum drying oven, set the temperature to 70° C., and dry for 10 hours to obtain a dry film.
[0059] (4) Immerse the glass sheet with the dry film in step (3) in deionized water for film removal. After about 5 minutes, the film is separated from the glass sheet. After taking it out, use filter paper to absorb the water on the surface of the film, and then dry it naturally to obtain a solid porous polymer film.
[0060] The average thickness of the solid porous polymer membrane prepared in this example was measured to be 100 μm, and the water contact angle was 94°, showing hydrophobic properties. It was cut into discs with a diameter of 15 mm using a hydraulic slicer and placed in a glove box for later use. The scanning electron microscope image of the membrane surface is shown in FIG. Figure 1 As shown, it can be seen that the solid porous polymer membrane prepared in this embodiment has circular pores evenly distributed on the surface of the gas separation membrane, and the pore size is about 200-400 nm.
[0061] Example 2
[0062] The present embodiment is different from the embodiment 1 in that, in the present embodiment, PVDF-HFP is 2.7 g, PEO is 0.3 g, PEI is 1 g, and the solvent is 20 g.
[0063] Comparative Example 1
[0064] The difference between this comparative example and Example 1 is that PEI is not added in this comparative example. The surface scanning electron microscope image of the solid porous polymer membrane prepared in this comparative example is as follows: Figure 2 As shown, the pore size is about 400-600 nm and is evenly distributed on the membrane surface.
[0065] Comparative Example 2
[0066] The difference between this comparative example and Example 1 is that PEO is not added in this comparative example. The surface scanning electron microscope image of the polymer film prepared in this comparative example is as follows Figure 3 As shown, it can be seen that when PEO is not added, the membrane surface is dense and no obvious pores are observed.
[0067] Comparative Example 3
[0068] The difference between this comparative example and Example 1 is that in step (1) of this comparative example, stirring is performed at room temperature without heating. Figure 4As shown in a in FIG. 1 , it can be seen that the compatibility between PEO and the solvent is very poor, and there is undissolved polymer solid. The macroscopic photograph of the solid porous polymer film obtained in this comparative example is shown in FIG. Figure 5 As shown in a in the figure, it can be seen that the uniformity of the prepared solid porous polymer film is very poor. The macroscopic photograph of the solid porous polymer film of Example 1 is shown in FIG. Figure 5 As shown in b, it exhibits good uniformity.
[0069] Comparative Example 4
[0070] The difference between this comparative example and Example 1 is that in step (1) of this comparative example, the heating temperature is 50°C, the stirring speed is 400r / min, and the stirring is 8h. Figure 4 As shown in c, the casting solution prepared in Example 1 is as Figure 4 As shown in b, it can be seen that the heating and stirring time of this comparative example is too long, and the casting liquid undergoes gelation, while Example 1 obtains a uniform casting liquid.
[0071] Comparative Example 5
[0072] The difference between this comparative example and Example 1 is that the amount of PVDF-HFP is 2.4 g, the amount of PEO is 0.6 g, and the amount of PEI is 1 g.
[0073] The water contact angle of the solid porous polymer film prepared in this comparative example is 86.2°, indicating that the film is hydrophilic; its scanning electron microscope image is as follows Figure 6 As shown, it can be seen that the pores on the surface of the solid porous polymer membrane prepared in this comparative example are unevenly distributed and the pore sizes are uneven, and the number of pores is very small. It can be seen that an increase in the amount of PEO does not lead to an increase in pores, but will have an adverse effect on the pore structure of the membrane.
[0074] Test example
[0075] 1. Gas permeability test
[0076] The gas permeability test was performed on the solid porous polymer membrane of Example 1 and the solid porous polymer membrane of Comparative Example 1, as shown in Table 1.
[0077] Table 1 Gas permeability test results
[0078] serial number <![CDATA[O2 permeability (cm 3 / (m 2 ·d·Pa))]]> <![CDATA[CO2 permeability (cm 3 / (m 2 ·d·Pa))]]> Example 1 <![CDATA[2.699×10 -4 ]]> <![CDATA[1.579×10 -3 ]]> Comparative Example 1 <![CDATA[2.887×10 -4 ]]> <![CDATA[1.695×10 -3 ]]>
[0079] It can be seen from Table 1 that after adding PEI, the O2 permeability and CO2 permeability of the solid porous polymer membrane of Example 1 are both reduced compared with those of Comparative Example 1. This is mainly because the pore size of the membrane of Example 1 is smaller than that of the membrane of Comparative Example 1.
[0080] 2. Assembly and electrochemical performance testing of lithium-air batteries:
[0081] The solid porous polymer membrane of Example 1 and the solid porous polymer membrane of Comparative Example 1 were respectively assembled into lithium-air batteries as gas separation membranes (GSM). The schematic diagram of the battery assembly structure is shown in FIG. Figure 7 As shown, the gas separation membrane is arranged between the positive electrode shell and the air positive electrode. The air positive electrode is a CNT / RuO2 composite positive electrode, the electrolyte is 1M TEGDME-LiTFSI, and the metal negative electrode is a lithium sheet.
[0082] Assembly method: First, place a spring gasket and a steel sheet in the negative electrode shell, and place the lithium sheet on top of the steel sheet. Secondly, place the glass fiber membrane on the lithium sheet, drip 80uL of 1M TEGDME-LiTFSI organic electrolyte, and try to make the electrolyte evenly infiltrate the glass fiber membrane. Next, place the air positive electrode (CNT / RuO2 composite positive electrode) on the surface of the glass fiber membrane, and place the gas separation membrane on the surface of the positive electrode, keeping them concentric. Finally, cover the positive electrode shell on the above parts, and use a hydraulic tablet press to press the battery at 500psi.
[0083] The assembled lithium-air battery was subjected to the first cycle deep discharge / charge test. The test results are as follows: Figure 8 As shown. It can be seen from the figure: when the battery is directly exposed to the ambient air, the maximum discharge capacity of the battery is 10.49mAh, and the discharge voltage platform is stable at about 2.6V; the maximum charge capacity of the battery is 6.06mAh, and the charge voltage platform is stable at about 4.0V. When the battery is equipped with the gas separation membrane of Comparative Example 1, the maximum discharge capacity of the battery in the first cycle is 6.64mAh, and the discharge voltage platform is still stable at about 2.6V; the maximum charge capacity of the battery is 6.56mAh. When the battery is equipped with the gas separation membrane of Example 1, the maximum discharge capacity of the battery in the first cycle is 6.09mAh, and the discharge voltage platform is stable at about 2.6V; the maximum charge capacity of the battery is 5.82mAh. Although the discharge capacity of the battery assembled with the gas separation membranes of Example 1 and Comparative Example 1 is reduced, the effective charge capacity is not reduced.
[0084] The assembled lithium-air battery was subjected to constant capacity cycle discharge / charge test. The test results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that the battery equipped with the gas separation membrane of Comparative Example 1 continuously discharges / charges for 400 hours, while the battery equipped with the gas separation membrane of Example 1 continuously discharges / charges for 780 hours, and the lithium-air battery without the gas separation membrane only discharges / charges for 270 hours. This shows that the gas separation membrane provided in Example 1 of the present invention can effectively protect the battery and greatly extend the battery life. Its working principle is as follows: Fig.10As shown, the gas separation membrane is placed on the outside of the air positive electrode. Due to its good surface hydrophobicity, water vapor in the air slides on the membrane surface and cannot penetrate into the gas separation membrane. At the same time, since the membrane itself has good gas permeability, its surface pores provide a transmission channel for the gas required for the reaction, and filter part of CO2 under the porosity and adsorb part of CO2 under the action of PEI.
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a solid porous polymer membrane for a metal-air battery, characterized in that: The steps include: A fluorine-containing polymer, polyethylene oxide and polyethyleneimine in a mass ratio of (2.5-2.7):(0.3-0.5):1 are dissolved in a solvent to form a casting solution, and then the casting solution is coated on the surface of a substrate, dried and placed in water for demolding, and dried to obtain a solid porous polymer membrane for a metal-air battery.
2. The preparation method according to claim 1, characterized in that The fluorine-containing polymer includes one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) or polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE).
3. The preparation method according to claim 1, characterized in that: The weight average molecular weight of the fluorine-containing polymer is greater than 300,000, the weight average molecular weight of polyethylene oxide is greater than 800,000, and the weight average molecular weight of polyethyleneimine is 1,700-2,000.
4. The preparation method according to claim 1, characterized in that: The solvent is selected from one or more of acetone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone; in the casting solution, the total mass fraction of the fluorine-containing polymer, polyethylene oxide, and polyethyleneimine is 10-20wt%.
5. The preparation method according to any one of claims 1, characterized in that: The steps include: The specific steps of the preparation process of the casting solution are as follows: adding fluorine-containing polymer, polyethylene oxide and polyethyleneimine into a solvent, stirring at 40-60° C. for 3-6 hours, to obtain the casting solution.
6. The preparation method according to claim 1, characterized in that: In the step of coating the casting solution on the substrate surface, the coating thickness is 400-600 μm; in the step of placing the film in water for demolding after drying, the drying temperature is 60-100° C.; and the time for demolding in water is 2-10 minutes.
7. The preparation method according to claim 1, characterized in that: In the step of drying to obtain a solid porous polymer membrane for a metal-air battery, the drying temperature is 15 to 35°C.
8. A solid porous polymer membrane for a metal-air battery prepared by the preparation method according to any one of claims 1 to 7. 9 . Use of the solid porous polymer membrane for metal-air battery as claimed in claim 8 in metal-air battery.
10. A metal-air battery, characterized in that: It comprises a positive electrode shell, a gas separation membrane, a positive electrode, an electrolyte layer, a metal negative electrode, a steel sheet, a spring sheet and a negative electrode shell which are in contact with each other in sequence; the gas separation membrane is the solid porous polymer membrane for the metal-air battery as claimed in claim 8.
Citation Information
Patent Citations
Air metal fuel cell
CN107210503A
Gas separation membrane, manufacturing method thereof and cell having gas separation membrane
KR1020140051623A